G12V and G12A KRAS mutations are associated with poor outcome in patients with metastatic colorectal cancer treated with bevacizumab - Fiala, Ondrej; Buchler, Tomas; Mohelnikova-Duchonova, Beatrice; Melichar, Bohuslav; Matejka, Vit Martin; Holubec, Lubos; Kulhankova, Jana; Bortlicek, Zbynek; Bartouskova, Marie; Liska, Vaclav; Topolcan, Ondrej; Sedivcova, Monika; et al. (Tumour biology, 2016)
The v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations are found in 35-45 % of colorectal cancer (CRC) cases. Although the association between the RAS signaling and angiogenesis is well known, the negative predictive value of KRAS mutation has not been established in patients treated with bevacizumab. The aim of this study was to evaluate the association between specific KRAS mutation types and outcome of patients with metastatic CRC treated with bevacizumab. The study included 404 patients with metastatic CRC (mCRC) treated with bevacizumab. Clinical data obtained from the clinical registry CORECT were retrospectively analyzed. The shortest survival was observed in patients with tumors harboring G12V or G12A KRAS mutation (G12V/A). The median progression-free survival (PFS) and overall survival (OS) for patients with tumors harboring G12V/A KRAS mutation was 6.6 and 16.8 compared to 11.6 and 26.3 months for patients with tumors harboring other KRAS mutation type (p < 0.001 and p < 0.001), while the survival of patients harboring other KRAS mutation types was comparable to those with tumors harboring wild-type KRAS gene. In the Cox multivariable analysis, KRAS G12V/A mutation type remains a significant factor predicting both PFS (HR = 2.18, p < 0.001) and OS (HR = 2.58, p < 0.001). In conclusion, the results of the present study indicate that there is a significant difference in biological behavior between tumors harboring G12V/A and other KRAS mutations. Moreover, comparison of the survival of patients with tumors harboring G12V/A KRAS mutations with those harboring wild-type KRAS gene revealed that G12V/A KRAS mutations are prognostic biomarker for inferior PFS and OS in patients with mCRC treated with bevacizumab in univariate as well as multivariable analyses.
Keywords: mutace; dospělí; metastázy nádorů; Kaplan-Meier Estimate; kolorektální nádory; Female; ras Proteins; kombinovaná terapie; Adult; výsledek terapie; ženské pohlaví; Kaplanův-Meierův odhad; Colorectal Neoplasms; Retreatment; KRAS; lidé; bevacizumab; kodon; Chemotherapy; Mutation; Treatment Outcome; Aged, 80 and over; Codon; prognóza; Colorectal cancer; proporcionální rizikové modely; Male; Bevacizumab; Combined Modality Therapy; Aged; opakovaná terapie; Proportional Hazards Models; alely; Prognosis; Alleles; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Neoplasm Metastasis; Middle Aged; Ras proteiny; Humans